1989
DOI: 10.1037/h0092456
|View full text |Cite
|
Sign up to set email alerts
|

Subfornical organ connectivity and drinking to captopril or carbachol in rats.

Abstract: These experiments were conducted to test whether drinking to ip captopril or to intraventricular carbachol requires an intact fiber system from the ventral subfornical organ (SFO). Wire-knife cuts were made through the wall of the third ventricle ventral to the SFO. Control rats had either sham lesions or histologically identified missed cuts. Rats with good cuts (a) drank less than either control group after ip injections of 4 mg/kg captopril, (b) drank normal amounts of 0.3 M NaCl solution when captopril was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 38 publications
5
28
1
Order By: Relevance
“…Extracellular dehydration was induced by subcutaneous injection of furosemide (10 mg/kg; Hospirca Lake Forest, IL) along with the antihypertensive drug captopril (5 mg/kg; Sigma Aldrich, St. Louis, MO), which results in a slight drop in blood pressure (ϳ10 mmHg) (31,50). Water was offered immediately after furo/cap treatment and 90 min later 1.8% NaCl access was added.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular dehydration was induced by subcutaneous injection of furosemide (10 mg/kg; Hospirca Lake Forest, IL) along with the antihypertensive drug captopril (5 mg/kg; Sigma Aldrich, St. Louis, MO), which results in a slight drop in blood pressure (ϳ10 mmHg) (31,50). Water was offered immediately after furo/cap treatment and 90 min later 1.8% NaCl access was added.…”
Section: Subjectsmentioning
confidence: 99%
“…Coadministration of the diuretic furosemide along with the antihypertensive drug captopril (furo/cap) causes an extracellular dehydration concomitant with a slight drop in blood pressure (31,50). These effects result in a rapid onset of thirst and sodium appetite with a latency of ϳ1 h (17,31,50).…”
mentioning
confidence: 99%
“…Consistent with this idea, Kisley and colleagues showed that pharmacological disruption of the genomic effects of estrogens reverses the attenuation of water intake stimulated by central administration of AngII [28]. Moreover, estradiol treatment reduces AngII receptor binding [27] and AngII receptor gene expression [32] in the subfornical organ (SFO), a forebrain circumventricular organ strongly implicated in drinking elicited by AngII [17,33,38]. Estradiol treatment also decreases isoproterenol-induced neuronal activation in the SFO [32].…”
Section: Introductionmentioning
confidence: 99%
“…The present study uses the expression of Fos-ir to map areas of the rat forebrain and hindbrain that become metabolically active in a protocol that stimulates thirst and salt appetite within a 3-h experimental period (8,16,33,34). In this procedure, animals are made hypovolemic by administration of a diuretic (i.e., furosemide).…”
mentioning
confidence: 99%